The Sensitive Skin Syndrome - Hadar Lev-Tov; Howard I Maibach (Wolters Kluwer Medknow Publications, 2012)
Sensitive skin syndrome (SSS) is a common and challenging condition, yet little is known about its underlying pathophysiology. Patients with SSS often present with subjective complaints of severe facial irritation, burning, and/or stinging after application of cosmetic products. These complaints are out of proportion to the objective clinical findings. Defined as a self-diagnosed condition lacking any specific objective findings, SSS is by definition difficult to quantify and, therefore, the scientific community has yet to identify an acceptable objective screening test. In this overview we review recent epidemiological studies, present current thinking on the pathophysiology leading to SSS, discuss the challenges SSS presents, and recommend a commonsense approach to management.